2018
DOI: 10.1002/aur.2041
|View full text |Cite
|
Sign up to set email alerts
|

Error monitoring in decision‐making and timing is disrupted in autism spectrum disorder

Abstract: Individuals with autism spectrum disorder (ASD) have difficulties in social interactions. The cognitive domains that support these interactions include perceptual decision‐making, timing, and error‐monitoring, which enable one to appropriately understand and react to the other individual in communicative settings. This study constitutes a comprehensive exploration of decision‐making and interval timing in ASD as well as the first investigation of error‐monitoring abilities of individuals with ASD regarding the… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

2
27
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 24 publications
(29 citation statements)
references
References 37 publications
2
27
0
Order By: Relevance
“…Our findings showed that in the absence of explicit feedback, humans can monitor the direction of errors in their reproductions of lengths (for nearly all targets) and their confidence ratings can track the magnitude of their errors for all target lengths. Together with our previous findings which indicate that humans can better than chance guess the direction and match their confidence to the degree of errors (based on composite measure) in their temporal (Akdoğan & Balcı, 2017; see also Doenyas, Mutluer, Genç, & Balcı, 2019;Kononowicz et al, 2018) and numerical (Duyan & Balcı, 2018) reproductions and numerical estimations (Duyan & Balcı, 2019), the results of Samaha and Postle (2017) that point toward a similar ability in relation to orientation judgment errors, and given converging evidence for a general magnitude representation system in the brain (Bueti & Walsh, 2009;Walsh, 2003), we surmise that this error monitoring ability would most likely extend to other metric domains.…”
Section: Discussionsupporting
confidence: 86%
“…Our findings showed that in the absence of explicit feedback, humans can monitor the direction of errors in their reproductions of lengths (for nearly all targets) and their confidence ratings can track the magnitude of their errors for all target lengths. Together with our previous findings which indicate that humans can better than chance guess the direction and match their confidence to the degree of errors (based on composite measure) in their temporal (Akdoğan & Balcı, 2017; see also Doenyas, Mutluer, Genç, & Balcı, 2019;Kononowicz et al, 2018) and numerical (Duyan & Balcı, 2018) reproductions and numerical estimations (Duyan & Balcı, 2019), the results of Samaha and Postle (2017) that point toward a similar ability in relation to orientation judgment errors, and given converging evidence for a general magnitude representation system in the brain (Bueti & Walsh, 2009;Walsh, 2003), we surmise that this error monitoring ability would most likely extend to other metric domains.…”
Section: Discussionsupporting
confidence: 86%
“…Performance-wise, ASD children achieved the task objectives and the mean reproduction accuracy and coefficient of variation demonstrated similarity to neurotypical children ( Doenyas et al 2019 ). However, there was a minimal match between the level of subjective self-confidence and actual objective performance in ASD children, suggesting that ASD children were unaware of temporal errors ( Doenyas et al 2019 ).…”
Section: Discussionmentioning
confidence: 89%
“…The findings of our study have implications for a more extensive understanding of clinical conditions when there is a disruption of the self-awareness of timing behavior. Doenyas et al (2019) reported on autistic spectrum disorder (ASD) children who performed a no-feedback version of the auditory temporal reproduction task that also used confidence ratings and self-assessment of underreproductions or overreproductions. Performance-wise, ASD children achieved the task objectives and the mean reproduction accuracy and coefficient of variation demonstrated similarity to neurotypical children ( Doenyas et al 2019 ).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Performancewise, ASD children achieved the task objectives and the mean reproduction accuracy and coefficient of variation demonstrated similarity to neurotypical children (Doenyas et.al, 2019). However, there was a minimal match between the level of subjective self-confidence and actual objective performance in ASD children, suggesting that ASD children were unaware of temporal errors (Doenyas et. al, 2019).…”
Section: Discussionmentioning
confidence: 99%